TOXICITY ASSESSMENT OF IMIDAZOLIUM-BASED IONIC LIQUIDS FAMILY USING MICROTOX - HAMID ALI, MOHAMMAD ASHRAF (IRC, 2019)
Researches on ionic liquids give focus on tuning their unique potential to suit industrial interest while at the same time, addressing the potential hazards associated with their toxicity to provide best selection of the ionic liquids with excellent performance while being inherently safe to the process and environment. This study the toxicity profile of three different ionic liquids from imidazolium family; 1-Decyl- 3-Methylimidazolium chloride (DMIM Cl) , 1-Butyl-3-Methylimidazolium Tetrafluoroborate (BMIM BF4) and 1-Ethyl-3-Methyl Imidazolium Octyl-Sulphate (EMIM OS). Stock solution of ionic liquids with dilution up to 10000 mg/L were tested using Microtox® toxicity test and bioluminescence bacteria, Vibrio Fischeri as the acute reagent. The EC50 value and inhibition plot had been determined by using Microtox 2% Basic test procedure.